Moving from the Oslerian paradigm to the post-genomic era: are asthma and COPD outdated terms? - Vanfleteren, L; Kocks, J; Stone, I; Breyer-Kohansal, R; Greulich, T; Lacedonia, D; Buhl, R; Fabbri, L; Pavord, I; Barnes, N; Wouters, E; Agusti, A (2014)
In the majority of cases, asthma and chronic obstructive pulmonary disease (COPD) are two clearly distinct disease entities. However, in some patients there may be significant overlap between the two conditions. This constitutes an important area of concern because these patients are generally excluded from randomised controlled trials (mostly because of smoking history in the case of asthma or because of significant bronchodilator reversibility in the case of COPD). As a result, their pathobiology, prognosis and response to therapy are largely unknown. This may lead to suboptimal management and can limit the development of more personalised therapeutic options. Emerging genetic and molecular information coupled with new bioinformatics capabilities provide novel information that can pave the way towards a new taxonomy of airway diseases. In this paper we question the current value of the terms 'asthma' and 'COPD' as still useful diagnostic labels; discuss the scientific and clinical progress made over the past few years towards unravelling the complexity of airway diseases, from the definition of clinical phenotypes and endotypes to a better understanding of cellular and molecular networks as key pathogenic elements of human diseases (so-called systems medicine); and summarise a number of ongoing studies with the potential to move the field towards a new taxonomy of airways diseases and, hopefully, a more personalised approach to medicine, in which the focus will shift from the current goal of treating diseases as best as possible to the so-called P4 medicine, a new type of medicine that is predictive, preventive, personalised and participatory.